THE EFFECT OF SERVICE QUALITY, FACILITIES AND RATE VALUE ON INPATIENT PATIENT SATISFACTION AT RSI WONOSOBO - Lusiana Ambarsari; Rosydah Rosydah; Rochana Ruliyandari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Background Patient satisfaction is an important indicator in assessing the success of hospital services, especially in inpatient services that demand continuous service. Quality of service, completeness of facilities, and appropriateness of tariff value are crucial factors that can affect patient perception and satisfaction. RSI Wonosobo as a private health service provider needs to continue to improve these three aspects to maintain patient trust and loyalty in the midst of competition between hospitals. Methods: used quantitative with a survey approach. Results: The study shows that service quality, facilities, and tariff value have a positive and significant effect on patient satisfaction partially and simultaneously. Service quality is the most dominant factor in influencing patient satisfaction. This study provides practical implications for the management of RSI Wonosobo to continue to improve aspects of service as part of a strategy to improve the quality of health services. Service quality, facilities, and tariff value have a positive and significant influence on inpatient satisfaction at RSI Wonosobo. Among the three factors, service quality is the most dominant factor. Therefore, to increase patient satisfaction and loyalty, hospital management needs to focus on improving service quality, facility comfort, and setting rates in accordance with patient expectations.Keywords: service quality, facilities, tariff value, patient satisfaction, inpatient care, RSI Wonosobo.